2003
DOI: 10.1063/1.1553466
|View full text |Cite
|
Sign up to set email alerts
|

Addition of water and methanol to Al3O3− studied by mass spectrometry and anion photoelectron spectroscopy

Abstract: The 4.66 eV photoelectron spectra of Al3O3−, Al3O3−⋅solvent and Al3O3−⋅(solvent)2 (solvent=H2O, D2O, and CH3OH) have been obtained and analyzed in the context of existing and preliminary new density functional theory calculations. The structures and vibrational frequencies of the two isomers of Al3O3− and Al3O3 proposed by Ghanty and Davidson [J. Phys. Chem. A 103, 8985 (1999)] agree well with structural information extracted from the Al3O3− spectra using Franck–Condon simulations. Photoelectron spectra of Al3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…This phenomenon of trapped, high-energy intermediates was observed previously in studies on aluminum suboxide clusters. [15][16][17] A number of water reactivity studies have been done on a range of transition metal atoms, metal clusters, and metal oxide clusters, most of which have been cationic. Not all species show high reactivity toward water, with many forming molecular complexes instead.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon of trapped, high-energy intermediates was observed previously in studies on aluminum suboxide clusters. [15][16][17] A number of water reactivity studies have been done on a range of transition metal atoms, metal clusters, and metal oxide clusters, most of which have been cationic. Not all species show high reactivity toward water, with many forming molecular complexes instead.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Aluminum oxide anions up to Al 7 O 5 − have been studied using anion photoelectron (APE) spectroscopy. [17][18][19][20][21] The APE spectra of the smaller anions are vibrationally resolved, and when combined with electronic structure calculations, they allowed identifying an Al-(O) 2 -Al rhombus as a common structural motif of small neutral and anionic dinuclear aluminum oxides. 18 Recently, vibrational and rotational molecular constants of AlO − were determined by means of autodetachment spec-troscopy.…”
Section: Introductionmentioning
confidence: 99%
“…37,39,40 Many excellent studies have been reported in the last decade with regard to the structure and reactivities of gas phase cationic 37,38, and anionic 42 [80][81][82] The groups of Wang and Jarrold performed detailed spectroscopic studies on aluminum oxide clusters. 76,[83][84][85][86][87] Rather interesting reactivity trends are reported by the Schwarz and Castleman groups for oxidation reactions generated by Al 2 O 3 + , 51,88,89 and methane activation by the oxygen-rich Al 2 O 7 + cluster suggests the importance and influence of chemically absorbed O 2 for the C-H bond activation reaction. 43 Other studies of gas phase cerium and aluminum oxide ionic clusters can be found in Refs.…”
Section: Introductionmentioning
confidence: 81%